SOCIOCULTURAL AND INDIVIDUAL DETERMINANTS OF ENTREPRENEURIAL INTENTIONS AMONG FEMALE STUDENTS IN TERTIARY INSTITUTIONS IN SOUTHWEST NIGERIA - Bamidele, Wale-Oshinowo (Universitas Mercu Buana Yogyakarta, 2025)
In Nigeria, interest in female entrepreneurship has grown in recent years, yet many studies have overlooked the subtler psychological and sociocultural factors that shape young women's entrepreneurial intentions. This study explores these factors by examining the interplay of individual traits and social context among female students in tertiary institutions in southwest Nigeria. The study employed a descriptive cross-sectional survey design. It engaged 385 female students in federal tertiary institutions across Southwestern Nigeria. The study used multiple regression analysis to assess the influence of variables such as self-efficacy, self-confidence, attitude, role models, family income, business family background, and ethnicity on entrepreneurial aspirations. Findings revealed that psychological traits, particularly self-confidence, self-efficacy, and entrepreneurial attitude, had positive, statistically significant relationships with entrepreneurial intention. Role models also emerged as a powerful sociocultural influence. While family income, business background, and ethnicity were significantly related to entrepreneurial intention, their effects were comparatively weaker. These results suggest that individual-level psychological factors are stronger drivers of entrepreneurial intentions in young Nigerian women when compared with sociocultural factors. The study focused on a specific region, Southwestern Nigeria, and the sample was limited to female students in federal tertiary institutions, which may affect the generalisability of the findings across different areas or populations. This study offers meaningful theoretical and practical insights by highlighting the nuanced ways individual and contextual elements converge in a dynamic developing country. It recommends the development of mentorship initiatives featuring successful female entrepreneurs to support and inspire the next generation of women business leaders.